A new approach for enhancing LSB steganography using bidirectional coding scheme - Mohammed M. Saeed Abdullah Al-Momin; Issa Ahmed Abed; Hussein A. Leftah (International Journal of Electrical and Computer Engineering (IJECE), 2019)
This paper proposes a new algorithm for embedding private information within a cover image. Unlike all other already existing algorithms, this one tends to employ the data of the carrier image more efficiently such that the image looks less distorted. As a consequence, the private data is maintained unperceived and the sent information stays unsuspicious.  This task is achieved by dividing the least significant bit plane of the cover image into fixed size blocks, and then embedding the required top-secret message within each block using one of two opposite ways depending on the extent of similarity of each block with the private information needed to be hidden. This technique will contribute to lessen the number of bits needed to be changed in the cover image to accommodate the private data, and hence will substantially reduce the   amount of distortion in the stego-image when compared to the classic LSB image steganography algorithms.